2014
DOI: 10.1371/journal.pone.0099357
|View full text |Cite
|
Sign up to set email alerts
|

First Insight into the Genotypic Diversity of Clinical Mycobacterium tuberculosis Isolates from Gansu Province, China

Abstract: BackgroundInvestigations of Mycobacterium tuberculosis genetic diversity in China have indicated a significant regional distribution. The aim of this study was to characterize the genotypes of clinical M. tuberculosis isolates obtained from Gansu, which has a special geographic location in China.Methodology/Principal FindingsA total of 467 clinical M. tuberculosis strains isolated in Gansu Province were genotyped by 15-locus mycobacterial interspersed repetitive units–variable number tandem repeats (MIRU-VNTR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
2
11
1
1
Order By: Relevance
“…In previous studies, the predominance of the Beijing/W genotype in China has been well described. The proportion of Beijing/W lineage strain infections has been reported to be 91.82% in Beijing [20], with similar predominance in provinces that neighbor Xinjiang [21,22] (69.34% in Sichuan, 96.3% in Tibet, 87.58% in Gansu, and 93.26% in Inner Mongolia). However, the Beijing/W lineage is less prevalent in countries that neighbor Xinjiang (6.09% in Russia [23], 50% in Mongolia [4], and 6% in Pakistan [24]).…”
Section: Discussionmentioning
confidence: 89%
“…In previous studies, the predominance of the Beijing/W genotype in China has been well described. The proportion of Beijing/W lineage strain infections has been reported to be 91.82% in Beijing [20], with similar predominance in provinces that neighbor Xinjiang [21,22] (69.34% in Sichuan, 96.3% in Tibet, 87.58% in Gansu, and 93.26% in Inner Mongolia). However, the Beijing/W lineage is less prevalent in countries that neighbor Xinjiang (6.09% in Russia [23], 50% in Mongolia [4], and 6% in Pakistan [24]).…”
Section: Discussionmentioning
confidence: 89%
“…However, a strain belonging to the CAS lineage was first identified in this study. The mainly prevalent region of the CAS family was India, which was also reported in Tibet, Xinjiang, Jiangsu, and Gansu in China. The transmission way of CAS MTB strain into Yunnan remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of Beijing genotype among most of northern regions was higher than 75%, we also found that Beijing genotype only accounted for 57.3% of MTB isolates in Xinjiang Uygur Autonomous Region [14]. In southern China, the prevalence of Beijing family in Zhejiang (71.6%) was lower than that in Jiangsu (80.5%) [16], Shanghai (79.3%) [17], and Jiangxi (76.7%) [18], while it was higher than that in Chongqing (66.7%) [20], Guangxi (61.9%) [21], Fujian (57.3%) [22], and Guizhou (54.0%) [613, 15, 19, 23] (Table 4). …”
Section: Discussionmentioning
confidence: 99%